2019
DOI: 10.1039/c9sc00756c
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive membrane activity of cyclic-peptide–polymer conjugates

Abstract: Cyclic peptide nanotubes were coupled to poly(oxazoline)s using a cleavable connection. Upon stimuli responsive detachment of the polymer an on-demand membrane activity could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 45 publications
(48 reference statements)
0
43
0
3
Order By: Relevance
“…Based on these findings, it was proposed that sequential NCLthiol-Michael addition could be employed to synthesise 3-arm mikto-arm star terpolymers, using a thioester functional polymer in the NCL step. To this end, an acid-functional PEtOx 37 (PEtOx-COOH, Mn = 3100 g/mol) was synthesised and transformed into its thioester (PEtOx-COSPh; 8). Integration of the aromatic signals from the thiophenyl group at 7.38 ppm in the 1 H NMR against the methylene side-chain signal at 2.32 ppm revealed that 95% of the chains contained the thioester group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, it was proposed that sequential NCLthiol-Michael addition could be employed to synthesise 3-arm mikto-arm star terpolymers, using a thioester functional polymer in the NCL step. To this end, an acid-functional PEtOx 37 (PEtOx-COOH, Mn = 3100 g/mol) was synthesised and transformed into its thioester (PEtOx-COSPh; 8). Integration of the aromatic signals from the thiophenyl group at 7.38 ppm in the 1 H NMR against the methylene side-chain signal at 2.32 ppm revealed that 95% of the chains contained the thioester group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…α-Methoxy-ω-amino-PEG (mPEG-NH2) was obtained from RAPP Polymere and used as received. ω-carboxylic acid poly(2-ethyl-2-oxazoline) (PEtOx30-COOH) 37 and N-acylated poly(aminoester) based oligomers (oligo(MeOx-alt-AA)nA, oligo(EtOx-alt-AA)nA, oligo(ButOx-alt-AA)nA) 38,39 were synthesised according to literature procedures.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Ein cyclisches Peptid-Polymer-Konjugat mit reversibler kovalenter Disulfidbindung und reduktionsinduzierter Membraninteraktion. Reproduziert von Literatur 16) . Lizensiert unter CC-BY Hühnereimodell (ex ovo) hinsichtlich ihrer Toxizität und Blutkompatibilität, wobei sie gute Bioverträglichkeit feststellten.…”
Section: Makromolekulare Chemieunclassified
“…Die Polymerhülle lässt sich unter reduktiven Bedingungen gezielt abspalten, was eine In-situ-Membranaktivität auf Abruf verspricht. 16) Rodriguez-Emmenegger und Mitarbeiter untersuchten die Selbstanordnung amphiphiler Janus-Dendrimere in Dendrimersome und deren Interaktion mit E.-coli-Bakterien. Dabei beobachteten sie Endozytose in einem nichtaktivierten Prozess.…”
Section: Makromolekulare Chemieunclassified
“…[30][31][32] In addition, the introduction of a responsive linker between the cyclic peptide and polymer would endow these materials with stimuli-responsive proper-ties, offering great potential regarding the application of on demand drug delivery systems and antimicrobial drugs, but has been rarely reported. [33] The pyridyl disulfide reaction chemistry, one of the most widely used conjugation chemistry, has been reported to be highly efficient, orthogonal to other conjugation chemistry, and applicable under mild conditions. In addition, this chemistry offers unique properties.…”
mentioning
confidence: 99%